Clarithromycin ion pair in a liposomal membrane to improve its stability and reduce its irritation caused by intravenous administration. (3rd March 2016) - Geng, Sicong; Liu, Xiaolin; Xu, Hang; Cai, Cuifang; Zhang, Yu; Yao, Qing; Xu, Helin; Gou, Jingxin; Yin, Tian; Xiao, Wei; Tang, Xing
ABSTRACT: Objective : The aim of this study was to improve the drug loading (DL) and stability of clarithromycin (CLA)-loaded liposomes, and reduce the irritation caused by intravenous administration of CLA. Methods : A CLA–cholesteryl hemisuccinate (CHEMS) ion pair (CIP) was prepared by the solvent evaporation method and confirmed by fourier transform infrared spectroscopy, 1 H-nuclear magnetic resonance, differential scanning calorimetry and X-ray powder diffraction. Subsequently, CIP liposomes (CIP-Lip) were prepared by the thin-film dispersion method and evaluated in terms of their size, zeta-potential, in vitro release, stability, in vitro antimicrobial activity and irritation. Results : The CIP-Lip exhibited a homogeneous round shape, and their size, ζ -potential, encapsulation efficiency (EE) and DL were 71.89 ± 2.6 nm, −9.91 ± 0.82 mV, 95.1 ± 1.5% and 7.8 ± 0.3%, respectively. The physical appearance and drug content of CIP-Lip over a three-month storage remained almost unchanged. The release of CLA in CIP-Lip was pH-dependent, with a more rapid release at pH 6.0 than at pH 7.4. Although the in vitro antimicrobial activity of CIP-Lip was comparable with free CLA, the irritation produced by CIP-Lip was significantly reduced compared with CLA solution. Conclusions : These findings suggest that CIP-Lip is a promising intravenous drug delivery system, especially on account of its high DL and reduced irritation.